Competências gerenciais de enfermeiros no contexto hospitalar: uma pesquisa-ação - Fioretti, Audrey Cristina [UNIFESP] (2018)
This research aimed to analyze the managerial competency profile required for Nursing Director position in hospital context, according to nurses’ perspectives. The first part of this study presents theoretical reflections on nursing management, nurses’ management competencies, and the managerial competencies for technical leaders mapped by the Regional Nursing Council. As a method of approach to study object, a qualitative research was developed. The focus group was used from four thematic nuclei with six nurses in director position. The data were worked by content analysis. Thus, the need to develop a continuing education program for the training of nursing directors in the hospital context, in order to develop the basic competencies for professional practice, emerges